A Novel Sustainable Flour Derived Hierarchical Nitrogen‐Doped Porous Carbon/Polyaniline Electrode for Advanced Asymmetric Supercapacitors. Issue 20 (25th July 2016) - Yu, Pingping; Zhang, Zhiming; Zheng, Lingxia; Teng, Feng; Hu, Linfeng; Fang, Xiaosheng
Abstract : Hierarchically porous nitrogen‐doped carbon (HPC)/polyaniline (PANI) nanowire arrays nanocomposites are synthesized by a facile in situ polymerization. 3D interconnected honeycomb‐like HPC was prepared by a cost‐effective route via one‐step carbonization using urea and alkali‐treated wheat flour as carbon precursor with a high specific surface area (1294 m 2 g −1 ). The specific capacitances of HPC and HPC/PANI (with a surface area of 923 m 2 g −1 ) electrode are 383 and 1080 F g −1 in 1m H2 SO4, respectively. Furthermore, an asymmetric supercapacitor based on HPC/PANI as positive electrode and HPC as negative electrode is successfully assembled with a voltage window of 0–1.8 V in 1m Na2 SO4 aqueous electrolyte, exhibiting high specific capacitance (134 F g −1 ), high energy density (60.3 Wh kg −1 ) and power density (18 kW kg −1 ), and excellent cycling stability (91.6% capacitance retention after 5000 cycles). Abstract : An asymmetric supercapacitor based on hierarchically porous nitrogen‐doped carbon (HPC) as negative electrode and HPC/polyaniline nanowire arrays nanocomposites as positive electrode is successfully assembled, exhibiting high specific capacitance (134 F g −1 ), high energy density (60.3 Wh kg −1 ), and power density (18 KW kg −1 ), and excellent cycling stability (91.6% capacitance retention after 5000 cycles).